(untitled) (Journal of Veterinary Medicine and Animal Production, 2022)
U. of K. J. Vet. Med. Anim. Prod., Vol. 5, Issue 2 (2014) p 58-65ISSN: 24345658Performance and Blood Chemistry as Affected by Inclusion of MoringaOleifera Leaf Meal in Broiler chicks DietSafa M.A. El Tazi* and Ibrahim M. Tibin1AbstractThe effect of Moringa oleifera leaf meal (MOLM) on the performance and blood chemistryof broiler chicks’ diets were investigated. A total of one-hundred and sixty one-day old, unsexed(Ross) broiler chicks were randomly divided into four experimental groups. Each group was furthersubdivided into five replicates at the rate of eight chicks per pen in randomized complete blockdesign. Four levels of Moringa oleifera leaf meal (0.0, 3, 5 and 7%) were fed during theexperimental period for 7-weeks duration. Birds fed on MOLM gained significantly (P<0.05) higherweight and superior feed conversion ratio than birds fed the control diet. No significant differencebetween birds fed on 3% & 5% (MOLM) diets regarding final body weight or body weight gain.Birds fed on (5% MOLM) diet showed the heaviest body weight, highest total feed intake with thebest feed conversion ratio. There were significant (P<0.05) differences among groups in packed cellvolume (PCV) and red blood cell (RBC) of the birds. The haemoglobin (HB), mean corpuscularvolume (MCV), mean corpuscular hemoglobin (MCH) and mean corpuscular haemoglobinconcentration (MCHC) counts showed no significant (P>0.05) difference among treatments. Therewere significant (P<0.05) differences in the values of total protein supplementary serum, whilethere were no significant (P>0.05) differences in the values of serum albumin and globulin. Birdsfed on (5% MOLM) diet showed the highest values of (PCV), (RBC) and serum total protein ascompared to other experimental treatments. The highest profitability ratio (1.47) was obtained bythe diet with 5% (MOLM). Moringa oleifera leaf meal could be included at 5% dietary levelwithout any deterious effect on performance and blood characteristics of broilers